2024
DOI: 10.1111/ijfs.16937
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of wheat gluten wastewater: separation, characterisation, and solution rheology of arabinoxylans

Mengyuan Geng,
Jiale Li,
Denglin Luo
et al.

Abstract: SummaryA significant volume of gluten production wastewater, containing arabinoxylan, is generated during wheat processing, presenting an underutilised resource. In this study, water‐extractable arabinoxylan (WEAX) was obtained from this wastewater through water extraction and alcohol precipitation, followed by purification, and its chemical and rheological properties were subsequently investigated. The analysis revealed a mean molecular weight of 4.57 × 104 Da for WEAX, with arabinose (38.08%) and xylose (43.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our prior investigations have revealed that the extraction yield of WEAX crude extract from wheat gluten production wastewater (dry base) was determined to be 7.66%, whereas the yield of purified WEAX was diminished to 2.42%. Furthermore, the extracted pure WEAX was identified as a neutral polysaccharide possessing an average molecular weight of 4.57 × 10 4 Da, primarily consisting of xylose (43.77%), arabinose (38.08%), galactose (10.51%), and a minor proportion of glucose (5.86%) ( Geng et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior investigations have revealed that the extraction yield of WEAX crude extract from wheat gluten production wastewater (dry base) was determined to be 7.66%, whereas the yield of purified WEAX was diminished to 2.42%. Furthermore, the extracted pure WEAX was identified as a neutral polysaccharide possessing an average molecular weight of 4.57 × 10 4 Da, primarily consisting of xylose (43.77%), arabinose (38.08%), galactose (10.51%), and a minor proportion of glucose (5.86%) ( Geng et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to its biocompatibility, film-forming ability, and solubility, WEAX is a promising material for film formation. Additionally, our previous study has investigated the separation, characterization, and rheological properties of arabinoxylans from wheat gluten wastewater, and reported its antidiabetic activity based on the results of liver metabolism in type 2 diabetic mice ( Geng et al, 2024 ; Luo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%